DETECTION OF LAND USE CHANGES USING LANDSAT 8 COMPOSITE BAND 4,3,2 AND BAND 7,6,4 COMPOSITE IMAGES IN 2019 AND 2022 USING THE METHODPOST- CLASSIFICATION COMPARISSON PADANG CITY REGION - saputra, eko bima; putri, sri kandi; ernawati, ernawati; febriandi, febriandi (Remote Sensing Technology Study Program, 2024)
This study aims to 1) determine the area of land use in the city of Padang in 2019 and 2022 using the 4,3,2 (True Color) composite. 2) to determine the area of land use in Padang City in 2019 and 2022 using composite 7,6,4 (False Colour). 3) to find out changes in land use in the City of Padang in 2019 and 2022 using the Post- Classification Comparisson method. Processing is done using Landsat 8 satellite imagery downloaded from the USGS website. Before performing image interpretation, radiometric correction, atmospheric correction and geometric correction are carried out as well as band composite and satellite image cropping with the boundaries of the study area, namely the administrative boundaries of the City of Padang. The interpretation process is carried out using the Maximum Likelihood method using digital image processing applications and Geographic Information Systems (GIS). Change detection analysis method through Post-Classification Comparisson. Accuracy sampling was carried out systematically random sampling with the confusion matrix accuracy test technique. The results of the study in the Padang City area which has an area of 694.96 km2, Land use changes using Composite Band 4,3,2 Mixed Forests experienced a reduction of around 157.58Ha. Open land increased by around 48.85 Ha, rice fields decreased by 397.84 Ha. built-up area increased by around 94.12 Ha. Shrubs and shrubs, an increase of about 412.45 Ha. Changes in land use using Composite Band 7,6,4 Mixed Forest experienced a reduction of around 155.32 Ha. Open land increased by around 48.70 Ha. paddy fields decreased by 399.03 Ha. built-up area increased by around 94.83 Ha. Shrubs and shrubs increased by around 410.82 Ha of rivers in 2019 and in 2022 there will be no change with an area of 437.33 Ha.